Luffa–Ni/Al layered double hydroxide bio-nanocomposite for efficient ibuprofen removal from aqueous solution: Kinetic, equilibrium, thermodynamic studies and GEP modeling - Soheil Tavassoli; Afsaneh Mollahosseini; Saeed Damiri; Mehrshad Samadi (Heliyon)
Luffa is a robust, renewable biomaterial known for its low mass, high specific strength, and non-toxicity, making it ideal for composite development. This study modified luffa to create the LF@ppy@LDH nanocomposite, combining luffa, polypyrrole, and layered double hydroxides to efficiently remove ibuprofen from water. Techniques like FE-SEM, EDX, FTIR, and XRD confirmed the modification. To optimize adsorption efficiency, factors such as contact time (Ctime), adsorbent dosage (Ad), drug concentration (Dc), temperature (θ), stirring rate (Sr), and pH were carefully fine-tuned to maximize efficiency. The highest ibuprofen removal occurred at pH 5, with an adsorption capacity of 44.306 mg/g at 298 K. The Temkin isotherm model, which points to chemisorption as the mechanism, accurately depicted the adsorption process with a high correlation coefficient (R2 = 0.984). Moreover, the Elovich kinetic model proved to be the most precise in describing how ibuprofen adheres to the modified luffa, showing a very tight fit with the data (R2 = 0.993). LF@ppy@LDH demonstrated outstanding reusability, maintaining steady adsorption over five repeated rounds. In addition, a powerful data-driven model, namely gene expression programming (GEP), was employed to provide an explicit formula relating input variables to removal efficiency, highlighting the potential of LF@ppy@LDH for water purification and environmental remediation.